APPLICATION OF A BAYESIAN APPROACH IN GIS BASED MODEL FOR EVALUATING LANDSLIDE SUSCEPTIBILITY. CASE STUDY KIMI AREA, EUBOEA, GREECE - Ilia, I.; Tsangaratos, P.; Koumantakis, I.; Rozos, D. (Bulletin of the Geological Society of Greece, 2010)
The purpose of this study is to present a Bayesian approach (weight-of-evidence method) that utilizes GIS and employs statistical analysis in defining the main factors contributing to the occurrence of landslides in Kimi, Euboea, Greece and to calculate the probability for future landslide manifestation. Landslide locations were identified from field surveys and interpretation of aerial photographs. Additional data were collected from various sources (topographic, geological, land cover maps etc.) and introduced into a spatial database using GIS technology. The above data sources have been used to generate various thematic data layers that have been resample to 20x20 m2 grid size. Applying the developed methodology it was possible to generate appropriate susceptibility map and thus to predict areas of instability. The results of the analysis were verified using the landslide location data, showing a satisfactory agreement between expected and existing data on landslide location. The outcomes could be used to reduce associated hazards, and to plan land use construction.